Pengaruh Literasi Digital terhadap Minat Berwirausaha Mahasiswa di Era Society 5.0 - Feti Fatonah; Dwi Mulyono; Rifqi Fathin Al Hamid; Teguh Raharjo Triatmojo; Yurika Viona Putri (Peneliti.net, 2026)
The advancement of digital technology in the Society 5.0 era has brought significant impacts across various aspects of life, including education and entrepreneurship. As future leaders, students are expected to possess digital literacy skills that go beyond technical abilities, encompassing critical thinking, creativity, and innovation in utilizing technology to create new economic opportunities. This study aims to examine the extent to which digital literacy influences students’ entrepreneurial interest in the context of Society 5.0. The research employs a quantitative approach with a descriptive correlational design. A total of 13 students were selected as respondents using purposive sampling techniques. Data were collected through a Likert-scale questionnaire measuring digital literacy and entrepreneurial interest variables. The collected data were then analyzed using Pearson correlation and simple regression tests. The results reveal a positive and significant relationship between digital literacy and entrepreneurial interest (r = 0.62; p < 0.05). This indicates that the higher the students’ level of digital literacy, the greater their interest in entrepreneurship. Therefore, the findings highlight the importance of strengthening digital literacy within higher education curricula to foster innovative, adaptive, and competitive entrepreneurial mindsets among students in the era of Society 5.0.